Legal Review of The Doctrine of Undue Influence (Abuse of Circumstances) in E-Commerce Agreements with Standard Clauses - Mega Arum Saputri; Agus Prasetia Wiranto (UNISSULA Semarang, 2026)
This study aims to analyze the application of the doctrine of undue influence or abuse of circumstances (misbruik van omstandigheden) in e-commerce agreements that use standard clauses as the primary instrument of legal relations between business actors and consumers in the digital era. The development of electronic transactions has encouraged the use of standard clauses for efficiency, speed, and standardization of services, but on the other hand, raises serious issues related to consumer protection. Standard clauses in digital platforms often place consumers in a